Type patterns among active members of the Anglican Church: A perspective from England - Francis, Leslie J. (Mental health, religion & culture, 2007)
This study extends previous research among religious groups by reporting on psychological type patterns among both male and female active church members in England. A sample of 93 female and 65 male active members of the Anglican Church in England completed Form G (Anglicized) of the MBTI. Among the women, there were clear preferences for introversion, sensing, feeling, and judging. Among the men, there were clear preferences for introversion, thinking, and judging, but a balance between sensing and intuition. The predominant type among the women was ISFJ (22%), and the predominant type among the men was ISTJ (17%).